1993
DOI: 10.1111/j.1472-765x.1993.tb00381.x
|View full text |Cite
|
Sign up to set email alerts
|

A rapid method of evaluating permeabilizing activity against Pseudomonas aeruginosa

Abstract: A rapid (< 30 min) spectrophotometric method has been used to assess the ability of chemical agents to permeabilize the outer membrane of Pseudomonas aeruginosa. When permeabilized, the cells are rendered readily sensitive to lysozyme, an enzyme that is normally excluded from the peptidoglycan of this organism. In addition to ethylenediamine tetraacetic acid, substances showing permeabilizing activity were citric, isocitric, malic and gluconic acids (but not gluconic acid lactone) and sodium polyphosphate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
20
1

Year Published

1998
1998
2021
2021

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 6 publications
5
20
1
Order By: Relevance
“…2000) have also been evaluated with conductance technique in broths and milk, respectively. Due to these reasons, the impedimetric method is recognized as an alternative rapid method not only for screening the biocide activity of novel antimicrobial agents, but also for estimation of growth kinetics in mathematical modeling (Ayres et al. 1993, 1998; Johansen et al.…”
Section: Introductionmentioning
confidence: 99%
“…2000) have also been evaluated with conductance technique in broths and milk, respectively. Due to these reasons, the impedimetric method is recognized as an alternative rapid method not only for screening the biocide activity of novel antimicrobial agents, but also for estimation of growth kinetics in mathematical modeling (Ayres et al. 1993, 1998; Johansen et al.…”
Section: Introductionmentioning
confidence: 99%
“…Previous work (Ayres et al 1993) has demonstrated that EDTA and other potential permeabilizing agents induced lysozyme sensitivity in a strain of Ps. aeruginosa.…”
Section: Introductionmentioning
confidence: 99%
“…The outer membrane (OM) of Ps. aeruginosa requires a high concentration of Mg 2¦ cations for stabilization (Brown 1975) and cells are prone to lysis by chelating agents (Ayres et al 1993). External Mg 2¦ antagonizes EDTA or competes with OM Mg 2¦ for the chelator (Vaara and Jaakkola 1989;Vaara 1992).…”
Section: Introductionmentioning
confidence: 99%
“…During a 0.25 mg/L ozonated water treatment, the number of vesicles on cell surfaces also increased with an increase in contact time. Cell membrane permeation increased and extracellular constituents were more prevalent during the process, in Agent-induced lysis of P. aeruginosa cells exposed to ozone Cells treated with EDTA or other chelating agents are known to become sensitive to antibacterial agents to which they are usually resistant (13). Ironically, antibacterial agents also influence bacterial cell lysis induced by EDTA or other agents (14)(15)(16).…”
Section: Resultsmentioning
confidence: 97%